Energy analysis of a thermal system composed by a heat pump coupled with a PVT solar collector. (1st May 2019) - Vallati, A.; Ocłoń, P.; Colucci, C.; Mauri, L.; de Lieto Vollaro, R.; Taler, J.
Abstract: The development of heat pump technology in the tertiary sector can lead to a reduction in greenhouse emissions and enhanced exploitation of renewable energy sources, including solar energy. The present paper investigates the potentiality of an energy system equipped with photovoltaic thermal (PV) hybrid solar collectors, a storage tanks for the heat source and a heat pump for the space heating of a small office located in three different European cities. The behaviour of the heat pump according to the heat taken from the photovoltaic panels and stored in the tank has been analysed. An energy analysis was performed according to the efficiency of the heat pump and then the thermodynamic parameters of the system were evaluated. The analytical model of each subsystem of the thermal plant was developed in Matlab where hourly simulation during the period of heating season were performed. Therefore, a comparison between the results obtained for Rome, Milan and Cracow provided the heating energy demand covering rate for each of the cities in different subsystem efficiency conditions. When thermal and electrical efficiency of PVT are set respectively to 0.6 and 0.15 and the efficiency of storage unit heat exchanger is considered equal to 0.9 the heating demand covered for Rome is 70%, for Milan is 62%, while for Cracow is 47%. Those values show a good potential for supporting heat-pump based PV-T heating systems. Highlights: A novel combined PV-T heat pump system for supporting building heating is proposed. A mathematical model of the system is developed. The system performance is studied for three different locations: Cracow, Milan and Rome. The system heating efficiency is the highest in Rome, while the lowest in Cracow.